Synthesis and odour perception of a series of highly substituted cyclohexane derivatives. (26th November 2021) - Saget, Raphaël; Jaunky, Piotr; Plessis, Caroline; Duñach, Elisabet
Abstract: A series of novel‐substituted cyclohexane derivatives has been prepared and their olfactory evaluation is presented. The different structures are derived from the cyclization of an unsaturated ketal under catalytic conditions. Its further functionalization allowed for the preparation of a series of 22 new compounds. Most of the new cyclic compounds present fruity and/or woody notes. Abstract : A series of 22 novel‐substituted cyclohexane derivatives has been prepared and their olfactory evaluation is presented. Most of the new cyclic compounds present fruity and/or woody notes.